MIPAS: An instrument for atmospheric and climate research - Fischer, H; Birk, M; Blom, C; Carli, B; Carlotti, M; Von Clarmann, T; Delbouille, L; Dudhia, A; Ehhalt, D; Endemann, M; Flaud, J; Gessner, R; et al. (2008)
MIPAS, the Michelson Interferometer for Passive Atmospheric Sounding, is a mid-infrared emission spectrometer which is part of the core payload of ENVISAT. It is a limb sounder, i.e. it scans across the horizon detecting atmospheric spectral radiances which are inverted to vertical temperature, trace species and cloud distributions. These data can be used for scientific investigations in various research fields including dynamics and chemistry in the altitude region between upper troposphere and lower thermosphere. The instrument is a well calibrated and characterized Fourier transform spectrometer which is able to detect many trace constituents simultaneously. The different concepts of retrieval methods are described including multi-target and two-dimensional retrievals. Operationally generated data sets consist of temperature, H2O, O3, CH4, N2O, HNO3, and NO2 profiles. Measurement errors are investigated in detail and random and systematic errors are specified. The results are validated by independent instrumentation which has been operated at ground stations or aboard balloon gondolas and aircraft. Intercomparisons of MIPAS measurements with other satellite data have been carried out, too. As a result, it has been proven that the MIPAS data are of good quality. MIPAS can be operated in different measurement modes in order to optimize the scientific output. Due to the wealth of information in the MIPAS spectra, many scientific results have already been published. They include intercomparisons of temperature distributions with ECMWF data, the derivation of the whole NOy family, the study of atmospheric processes during the Antarctic vortex split in September∼2002, the determination of properties of Polar Stratospheric Clouds, the downward transport of NOx in the middle atmosphere, the stratosphere- troposphere exchange, the influence of solar variability on the middle atmosphere, and the observation of Non-LTE effects in the mesosphere.